Household Income Inequality in Poland from 2005 to 2013 – A Decomposition of the Gini Coefficient by Socio-Economic Groups - Graca-Gelert, Patrycja (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The aim of this study is the empirical analysis of the Gini coefficient decomposition by socio-economic groups in Poland from 2005 to 2013. The analysis was based on non-identifiable, individual household budget surveys data collected by Poland’s Central Statistical Office. For the purpose of this study income was defined as equivalized household disposable income, i.e. the unit of analysis is a household and household disposable income was adjusted using the OECD modified equivalence scale. The Gini coefficient decomposition by socio-economic groups revealed that the residual term measuring the extent to which overall inequality is attributable to overlapping income distributions of individual socio-economic groups contributed to the greatest extent to overall income inequality in Poland during the analyzed period. The second most important factor explaining income inequality was the component of inequality within socio-economic groups. Income inequality between socio-economic groups contributed about 28–30% to overall income inequality in Poland from 2015 to 2015. The Gini decomposition results allow to conclude, that the structure of the contribution of individual socio-economic groups in Poland was the following. Employees’ households were the group with the largest, increasing contribution of weighted income variability to overall income disparities. The second group that was explaining total income disparities to the greatest extent regarding within-inequality were old-age pensioners. The remaining socio-economic groups had only a marginal impact in this regard in Poland from 2005 to 2013.

Celem pracy jest przeprowadzenie dekompozycji współczynnika Giniego ze względu na grupy społeczno-ekonomiczne w Polsce w latach 2005-2013. Badanie przeprowadzono na nieidentyfikowalnych, jednostkowych danych pochodzących z badań budżetów gospodarstw domowych GUS. W niniejszym studium przez pojęcie dochód należy rozumieć dochód do dyspozycji gospodarstw domowych na jednostkę ekwiwalentną, tj. za badaną jednostkę przyjęto gospodarstwo domowe, za dochód – dochód do dyspozycji, przy czym zastosowano zmodyfikowaną skalę ekwiwalentności OECD. Dekompozycja współczynnika Giniego według grup społeczno-ekonomicznych pokazała, że największy wkład w kształtowanie się nierówności dochodów ogółem w Polsce w badanym okresie miał składnik resztkowy, czyli efekt wynikający z nakładania się dystrybucji dochodów poszczególnych grup społeczno-ekonomicznych. Drugim, co do istotności czynnikiem wyjaśniającym zróżnicowanie dochodów zgodnie z dekompozycją współczynnika Giniego według grup społeczno-ekonomicznych były nierówności wewnątrzgrupowe. Wkład nierówności międzygrupowych stanowił około 28-30% zróżnicowania dochodów ogółem w Polsce w badanym okresie. Uzyskane wyniki pozwoliły stwierdzić, że w badanym okresie struktura wkładu poszczególnych grup społeczno-ekonomicznych w wyjaśnianiu nierówności dochodów ogółem w Polsce kształtowała się następująco. Do grupy o największym, rosnącym wkładzie nierówności dochodów ważonych udziałami w populacji i dochodzie ogółem należały gospodarstwa domowe pracowników. Ważone zróżnicowanie dochodów dla gospodarstw domowych emerytów wyjaśniało nierówności ogółem w drugiej kolejności spośród badanych grup ekonomiczno-społecznych, mimo że grupa ta charakteryzowała się najniższym zróżnicowaniem dochodów w badanym okresie. Ważone nierówności dochodów pozostałych grup społeczno-ekonomicznych miały bardzo niewielkie znaczenie, jeśli chodzi o wkład w zróżnicowanie dochodów ogółem w Polsce w latach 2005–2013.
Keywords: income inequality; Gini coefficient; decomposition; nierówności dochodów; współczynnik Giniego; dekompozycja